The Rationality of Reluctance and Indifference Toward Adult Education: Difficulties in Recruiting Unemployed Adults to Adult Education - Sam Paladanius (Adult Education Research Conference, 2007)
This work presents the findings of a 2002 Swedish study of barriers to participation in adult education. The study questions why some members of the target group for the Swedish government’s Adult Education Initiative (AEI) – unemployed adults lacking upper secondary education – chose not to participate in programs.